2006
DOI: 10.22230/cjc.2006v31n2a1743
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Journalism “Excellent”? Criteria Identified by Judges in Two Leading Awards Programs

Abstract: What does "excellence" mean in journalism? The literature reveals no universally agreed set of standards, and awards guidelines are often unclear. We interviewed judges in two leading Canadian print journalism awards programs, using a sequence of open-ended and ranking questions to probe their criteria of excellence in a way calculated to elicit not just the standards they felt should be applied but the standards they actually did apply. Judges mentioned a wide variety of criteria, including the social importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Although the criteria for quality journalism have traditionally been tacit, intuitive, and varied rather than codified or standardized (Ruellan, 2007;Schultz, 2007;Shapiro, 2010;Shapiro, Albanese & Doyle, 2006;Soloski, 1989), several studies have shown that, even across cultural and socio-demographic lines, journalists tend to share core professional values (Pritchard, Brewer & Sauvageau, 2005;Weaver & Wu, 1998). The trend toward a unified set of values has been associated with globalization (Hanitzsch, 2007) and professionalization (Deuze, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the criteria for quality journalism have traditionally been tacit, intuitive, and varied rather than codified or standardized (Ruellan, 2007;Schultz, 2007;Shapiro, 2010;Shapiro, Albanese & Doyle, 2006;Soloski, 1989), several studies have shown that, even across cultural and socio-demographic lines, journalists tend to share core professional values (Pritchard, Brewer & Sauvageau, 2005;Weaver & Wu, 1998). The trend toward a unified set of values has been associated with globalization (Hanitzsch, 2007) and professionalization (Deuze, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The trend toward a unified set of values has been associated with globalization (Hanitzsch, 2007) and professionalization (Deuze, 2005). And the single most frequently and clearly stated value expressed in journalists' self-identification is a drive for accuracy (Bogart, 2004;Cleghorn, 1990;Davies, 2008;Franklin, 2006;Gladney, Shapiro & Castaldo, 2007;Meyer, 2004;Shapiro et al, 2006). This focus on accuracy as a key identifying professional characteristic in turn requires that journalistic methodology be centred to some degree on verification.…”
Section: Introductionmentioning
confidence: 99%
“…Shapiro, Albanese and Doyle interviewed jurors in two journalism awards programs and produced ranked lists of criteria that included writing and storytelling technique and rigour in reporting among the jurors' consistently top-of-mind indicators, and, substantially behind those two: originality; public impact and benefit to society; insight; analysis; context; balance or fairness; independence and integrity; and transparency of method (Shapiro et al, 2006).…”
Section: ''Quality'' and ''Excellence'' Surveysmentioning
confidence: 99%
“…40, 44). Judges of journalism awards, too, have indicated that they rely partly or largely on indefinable factors in identifying excellence (Shapiro et al, 2006). Likewise, Gardner, Csikszentmihalyi and Damon, after interviewing reporters, editors, their audiences, scholars, and shareholders of media corporations, reported that while other professions had achieved a high degree of alignment between the generally accepted values of the profession and those of the culture in which they worked, the field of journalism was ''wracked with tension.''…”
Section: Introductionmentioning
confidence: 99%
“…A few exceptions include the following: an early study by Beam, Dunwoody, and Kosicki (1986) that investigates the relationship between award winning and job satisfaction; a study by Coulson (1989) that examines American editors' attitudes toward journalism awards; and a study by Shapiro, Albanese, and Doyle (2006) that focuses on the winning criteria identified by Canadian judges. A large set of questions remains: how is journalistic excellence defined through an awarding system that embodies or defies the political, cultural, socio-economic, and journalistic traditions?…”
mentioning
confidence: 99%